No adaptation to warming after selection for 800 generations in the coccolithophore Emiliania huxleyi BOF 92 - Zhou, Cong; Zhang, Di; Yi, Xiangqi; Beardall, John; Gao, Kunshan (Frontiers in Marine Science, 2023)
Ocean warming is suggested to exert profound effects on phytoplankton physiology and growth. Here, we investigated how the coccolithophore Emiliania huxleyi (BOF 92, a non-calcifying strain) responded to changes in temperature in short- and long-term thermal treatments. The specific growth rate after 10 days of acclimation increased gradually with increasing temperatures (14, 17, 21, 24, 28°C) and peaked at ~23°C, followed by a significant decrease to 28°C. Chlorophyll a content, cell size, photosynthetic rate, and respiratory rate increased significantly from 14°C to 24°C, but the cellular particulate organic carbon (POC) and nitrogen (PON) showed the lowest values at the optimal temperature. In contrast, during long-term thermal treatments at 17°C and 21°C for 656 days (~790 generations for 17°C treatment; ~830 generations for 21°C treatment), the warming significantly stimulated the growth in the first 34 days and the last 162 days, but there was no significant difference in specific growth rate from Day 35 to Day 493. Chlorophyll a content, cell size, cellular POC/PON, and the ratio of POC to PON, showed no significant difference between the warming and control for most of the duration of the long-term exposure. The warming-selected population did not acquire persistent traits in terms of growth and cell quotas of POC and PON, which resumed to the levels in the control temperature treatment after about 9 generations in the shift test. In summary, our results indicate that warming by 4°C (17°C and 21°C) enhanced the growth, but did not result in adaptative changes in E. huxleyi (BOF 92) over a growth period of about 800 generations, reflecting that mild or non-stressful warming treatment to E. huxleyi isolated from cold seas does not alter its phenotypic plasticity.